Peningkatan Kinerja Guru dalam Menerapkan Model Pembelajaran Paikem Melalui Bimbingan Kelompok di SD Negeri 150/X Bukit Tempurung Semester Ganjil Tahun Ajaran 2022/2023 - Izziyati Izziyati (Departement of Mathematics Education, 2022)
This study aims to obtain information and discuss about improving teacher performance in implementing the paikem learning model through group guidance at SD Negeri 150/X Bukit Tempurung in the odd semester of the 2022/2023 academic year. This research is a school action research (PTS) which consists of two cycles. This research was conducted at SD Negeri 150/X Bukit Tempurung for the academic year 2022/2023 odd semester with 6 teachers as the subject of research. Data collection techniques using observation, field notes and documentation. Data were analyzed using percentages and data reduction. Based on the results of the research and discussion, it was concluded that group guidance can improve teacher performance in PAIKEM learning at SDN 150/X Bukit Tempurung which can be seen in each cycle by giving rewards. The increase in the percentage of completeness of data teacher performance seen in the first cycle was 69% (C) and increased in the second cycle, which was 89% (A)